A phase II study to assess the safety and efficacy of the dual mTORC1/2 inhibitor vistusertib in relapsed, refractory DLBCL. Issue 4 (9th September 2019) - Eyre, Toby A.; Hildyard, Catherine; Hamblin, Angela; Ali, Ayesha S.; Houlton, Aimee; Hopkins, Louise; Royston, Daniel; Linton, Kim M.; Pettitt, Andrew; Rule, Simon; Cwynarski, Kate; Barrington, Sally F.; et al.
Abstract: Patients with relapsed or refractory diffuse large B‐cell lymphoma (DLBCL) who are unfit for or relapsed postautologous stem‐cell transplantation have poor outcomes. Historically, mTORC1 inhibitors have produced responses in approximately 30% of patients in this setting. mTORC1 inhibitor efficacy may be limited by resistance mechanisms including AKT activation by mTORC2. To date, dual mTORC1/2 inhibitors targeting both the TORC1 and TORC2 complexes have not been investigated in DLBCL. This phase II trial investigated the oral dual mTORC1/2 inhibitor vistusertib in an intermittent dosing schedule of 125 mg b.d. for 2 days per week. Thirty patients received vistusertib and six received vistusertib‐rituximab for up to six cycles (28‐day cycles). Two partial responses were achieved on monotherapy. Durations of response were 57 and 62 days, respectively, for these patients. 19% had stable disease within six cycles. In the monotherapy arm, the median progression‐free survival was1.69 (95% confidence interval [CI] 1.61‐2.14) months and median overall survival was 6.58 (95% CI 3.81‐not reached) months, respectively. The median duration of response or stable disease across the trial duration was 153 days (95% CI 112‐not reached). Tumour responses according to positron emission tomography/computed tomography versus computed tomography were concordant. There were no differences noted in tumour volume response according to cell of origin by either gene expression profiling or immunohistochemistry. Vistusertib ± rituximab was well tolerated; across 36 patients 86% of adverse events were grade (G) 1‐2. Common vistusertib‐related adverse events were similar to those described with mTORC1 inhibitors: nausea (47% G1‐2), diarrhoea (27% G1‐2, 6% G3), fatigue (30% G1‐2, 3% G3), mucositis (25% G1‐2, 6% G3), vomiting (17% G1‐2), and dyspepsia (14% G1‐2). Dual mTORC1/2 inhibitors do not clearly confer an advantage over mTORC1 inhibitors in relapsed or refractory DLBCL. Potential resistance mechanisms are discussed within.